2021
DOI: 10.13057/biodiv/d220236
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and genetic parameter of chili pepper (Capsicum annuum) based on yield component in three location

Abstract: Abstract. Sayekti TWDA, Syukur M, Hidayat SH, Maharijaya A. 2021. Diversity and genetic parameter of chili pepper (Capsicum annuum) based on yield component in three locations. Biodiversitas 22: 823-829. With the increase in the use of chili, it is necessary to develop these commodities through plant breeding activities. Phenotypes are not only determined by genetics, but also by environmental factors and the GxE interactions, so all the factors need to be considered. The aims of this study were to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This variety produced relatively the same number of fruits when was grown in three different environments [17]. Other studies showed that the number of fruits variable in cayenne pepper has a high heritability value, around 97%, which means that the genetic influence is very large [17]. However, the phenotypic coefficient of variation and genotypic coefficient of variation for the number of fruits per plant variable is relatively the same, around 19.5%.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…This variety produced relatively the same number of fruits when was grown in three different environments [17]. Other studies showed that the number of fruits variable in cayenne pepper has a high heritability value, around 97%, which means that the genetic influence is very large [17]. However, the phenotypic coefficient of variation and genotypic coefficient of variation for the number of fruits per plant variable is relatively the same, around 19.5%.…”
Section: Resultsmentioning
confidence: 83%
“…The same result was shown by an earlier study on one of the OP varieties in Indonesia, Bara. This variety produced relatively the same number of fruits when was grown in three different environments [17]. Other studies showed that the number of fruits variable in cayenne pepper has a high heritability value, around 97%, which means that the genetic influence is very large [17].…”
Section: Resultsmentioning
confidence: 86%
“…Growth and production traits with high heritability values have also resulted in past studies for plant height, fruit diameter, number of fruit per plant, fruit weight, and fruit weight per plant (Qasim et al, 2013); plant height, stem diameter, flowering age, harvest age, fruit length, and fruit diameter (Syukur and Rosidah, 2014); and stem diameter and fruit length in cayenne pepper populations (Rosmaina et al, 2016). Traits, such as, fruit length, diameter, and weight with the highest genetic variation and heritability should be considered reliable selection criteria for increasing chili yields (Sayekti et al, 2021). High heritability values indicate that the influence of genetic factors was more significant and prevailing than environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…It is also linked to the adaptation of cellular osmotic potential (Pilon et al, 2019). Meanwhile, plants increased stomatal regulation to maintain internal water availability, which led to a decrease in stomatal index and leaf size to limit water loss (Lestari et al, 2023).…”
Section: Screening Based On Ratio Among Water Stress To Unstressedmentioning
confidence: 99%
“…In this study, the tolerant and susceptible cultivars were evaluated by examining the phenotypic characters as an initial screening process. Lestari et al (2023) reported that genetic factors had a greater influence on morpho-physiological traits under different environmental conditions. Genetic approaches are also needed to support early indication within screening research, such as the use of molecular markers as a tool to estimate the genetic diversity of plant species in the genomic era (Rini and Nuraisyah, 2021).…”
Section: Screening Based On Ratio Among Water Stress To Unstressedmentioning
confidence: 99%